FoxA2 involvement in suppression of protein C, an outcome predictor in experimental sepsis - Berg, David T; Gerlitz, Bruce; Sharma, Ganesh R; Richardson, Mark A; Stephens, Eddie J; Grubbs, Renee L; Holmes, Kimberly C; Fynboe, Kelly; Montani, Dominick; Cramer, Martin S; Engle, Steven D; Jakubowski, Joseph A; et al. (Clinical and vaccine immunology, 2006)
Low levels of protein C (PC) predict outcome as early as 10 h after insult in a rat polymicrobial sepsis model and were associated with suppression of PC mRNA, upstream transcription factor FoxA2, and cofactor hepatocyte nuclear factor 6 (HNF6). Small interfering RNA suppression of FoxA2 in isolated hepatocytes demonstrated regulation of both its cofactor HNF6 and PC. Our data suggest that reduced FoxA2 may be important in the suppression of PC and resulting poor outcome in sepsis.